Algorithm of Sliding Correlation-Spectral Analysis for the Pulse Wave Instantaneous Frequency Estimation - Labunets, Leonid V.; Ryakhina, Mariya Yu (International Youth Conference on Radio Electronics, Electrical and Power Engineering (REEPE ...) (Online), 2024)
This paper discusses methods and algorithms for studying the variability of the subject's heart rate by means of intelligent analysis of the pulse wave signal registered with remote photoplethysmography. Successive steps of obtaining the time series correlation-spectral characteristics considering the complex character of biomedical signals' time changes are presented. The aim of this study is to consider the content of intellectual digital signal processing of remote photoplethysmography signals, the methodology for estimating the instantaneous period of a quasi-harmonic pulse wave signal, as well as the application of these methods at the stage of the cardiovascular system diagnostic equipment development.